Multidisciplinary clinical guidance on trastuzumab deruxtecan (T-DXd)–related interstitial lung disease/pneumonitis—Focus on proactive monitoring, diagnosis, and management. (May 2022) - Swain, Sandra M.; Nishino, Mizuki; Lancaster, Lisa H.; Li, Bob T.; Nicholson, Andrew G.; Bartholmai, Brian J.; Naidoo, Jarushka; Schumacher-Wulf, Eva; Shitara, Kohei; Tsurutani, Junji; Conte, Pierfranco; Kato, Terufumi; et al.
Highlights: Drug-related interstitial lung disease (ILD)/pneumonitis diagnosis is challenging. Careful monitoring, prompt diagnosis, and appropriate management are important. Most events are low grade and can be managed safely. Education is critical to ensure potential ILD/pneumonitis is proactively identified. We suggest using a multidisciplinary approach. Abstract: Trastuzumab deruxtecan (T-DXd; DS-8201) is an antibody-drug conjugate targeting human epidermal growth factor receptor 2. Interstitial lung disease (ILD)/pneumonitis is an adverse event associated with T-DXd; in most cases, it is low grade (grade ≤ 2) and can be treated effectively but may develop to be fatal in some instances. It is important to increase patient and provider understanding of T-DXd–related ILD/pneumonitis to improve patient outcomes. Drug-related ILD/pneumonitis is a diagnosis of exclusion; other possible causes of lung injury/imaging findings must be ruled out for an accurate diagnosis. Symptoms can be nonspecific, and identifying early symptoms is challenging; therefore, diagnosis is often delayed. We reviewed characteristics of patients who developed T-DXd–related ILD/pneumonitis and its patterns, produced multidisciplinary guidelines on diagnosis and management, and described areas for future investigation. Ongoing studies are collecting data on T-DXd–related ILD/pneumonitis to further our understanding of its clinical patterns and mechanisms. Search strategy and selection criteria: References were identified based on the guidelines used by the authors in treating interstitial lung disease and pneumonitis. Searches of the authors' own files were also completed. A search of PubMed with the search terms (trastuzumab deruxtecan) AND (interstitial lung disease) AND (guidelines) was conducted on November 1, 2021, with no restrictions based on publication date, and the two articles yielded by the search were included.